The Translational Approaches to Personalized Health Collaborative: Pharmacogenomics for African American Older Adults. Issue 2 (7th October 2020) - J Sargent, Lana; Mackiewicz, Marissa; Roman, Youssef; Diallo, Ana; Russell, Sally; Falls, Katherine; Zimmerman, Kristin M.; Dixon, Dave L.; Prom‐Wormley, Elizabeth; Hobgood, Sarah; Lageman, Sarah K.; Zanjani, Faika; et al.
Abstract : Older adults (i.e., 60 years and older), are the leading consumers of medications, and consequently are suffering the most from medication‐related adverse events. Not only are older adults the largest consumers of medications, they are more likely to experience an adverse drug event contributing to increased hospitalization, utilization of emergency medical services, and mortality. Translational Approaches to Personalized Health (TAPH) is a transdisciplinary team of researchers conducting community‐engaged participatory research focused on the discovery and translation of pharmacogenomic (PGx) data to improve health outcomes. Underserved and ethnically diverse older adults living in urban settings are significantly under‐represented in PGx studies. To address the issue of under‐representation, our study enrolls older African American adults into a community‐based PGx study. Therefore, we will characterize the frequency of actionable PGx genotypes and identify novel PGx response genes in our cohort of older community dwelling African Americans. The translational component of our work is to use the PGx findings to improve therapeutic outcomes for medication management in older adults. Such findings will serve as a foundation for translational PGx studies aimed at improving medication efficacy and safety for older adults. In this article, we describe the process for launching the TAPH collaborative group, which includes the transdisciplinary team, community‐engaged participatory research model, study measures, and the evaluation of PGx genes.